Crystal structure of a solvated dinuclear CuII complex derived from 3,3,3′,3′-tetraethyl-1,1′-(furan-2,5-dicarbonyl)bis(thiourea) - Canh Dinh Le; Hoang Phuc Nguyen; Chien Thang Pham (My University, 2024)
Crystal structure of a solvated dinuclear CuII complex derived from 3,3,3′,3′-tetraethyl-1,1′-(furan-2,5-dicarbonyl)bis(thiourea)
Keywords: Dinuclear CuII